Neuronavigated theta burst stimulation for chronic aphasia: two exploratory case studies - Georgiou, Anastasios M.; Konstantinou, Nikos; Phinikettos, Ioannis; Kambanaros, Maria (My University, 2019)
The present study reports the findings of a 10-day neuronavigated continuous theta burst stimulation (cTBS) over the right pars triangularis for two individuals with chronic aphasia after a single left hemispheric stroke. Baseline language and quality of life measures were collected prior to the treatment study, post-treatment and at 3-month follow up. Therapy was tolerated well by both participants and no side effects were noticed during and after treatment. Results from one individual showed potential for positive change in performance in comprehension and expressive language both post-treatment and at the follow-up stage. Also, a trend towards improvement post-treatment was noticed in discourse and sentence productivity, and grammatical accuracy. In the follow up stage, grammatical accuracy showed a trend towards improvement; discourse productivity decreased and; sentence productivity skills showed mixed results. Results from the other participant showed potential for positive change in comprehension post-treatment, that was maintained at the follow-up stage. However, a decline in expressive language post-treatment and at follow-up, stronger post-treatment, was noticed. Regarding quality of life measurements, participant one appeared to have improved as his performance increased in the overall, physical and communication domains, but decreased slightly in the psychosocial domain. The second participant improved in the physical and communication domains and declined overall and in the psychosocial domains. Findings from this study indicate that cTBS over the right pars triangularis may have the potential to improve various language skills in patients suffering from chronic aphasia post-stroke. However, the potential benefits of this fast, non-invasive brain stimulation protocol on improvement of language abilities post-stroke need further exploration.
Keywords: Transcranial magnetic stimulation (TMS); Case-based approach; Neuronavigation; Quality of life; Receptive and expressive language